«Potrei scriverlo tutto in seconda persona». "Se una notte d’inverno un viaggiatore" come you-narrative (ENTHYMEMA, 2020)
In narratological terms, If on a Winter’s Night a Traveler is a you-narrative, that is, a narrative revolving around a ‘you’. This article aims at explaining both the way in which Calvino employed this formal device, and its importance within the textual construction. After focusing on the enunciative dynamics underlying the novel, I will reflect on the choice of a ‘you’ as part of a wider discourse concerning the relationship between author and reader, as well as the broader textual experience that Calvino aims to represent.
Keywords: you-narrative; metafiction; immersivity; reader; postmodernism